CLIMATE CHANGE MITIGATION THROUGH REAL ACTION OF RESTORATION GENERATION FOR MANGROVES ON LABU COASTLINE: MITIGASI PERUBAHAN IKLIM MELALUI AKSI NYATA GENERASI RESTORASI UNTUK MANGROVE DI PESISIR PANTAI LABU - Sri Malem Indirawati; Evi Naria; Surya Darma; Taufik Ashar; Devi Nuraini Santi; Nurmaini Nurmaini; Winni, R.E. Tumanggor; Indra Chahaya; Irnawati Marsaulina (Yayasan Education and Social Center, 2022)
Climate change causes an increase in waves and abrasion, damage to mangrove forests on the coast of Labu due to abrasion has an impact on the balance of coastal ecosystems. Mangrove forests function as breakwaters and abrasion resistance, spawning areas for marine life. This condition has an impact on the productivity of marine biota, the environment so that it will affect the community's economy. This community service aims to increase knowledge, skills and awareness of coastal communities in environmental management, especially mangrove conservation in overcoming abrasion, improving community values and changing behavior so that they can take an important role in climate change mitigation efforts. The method used is socialization, community development, mentoring and community organizing in environmental management through community service